The effects of mirror therapy on cross transfer of fine motor skills in healthy adults - Wong, Shu Fen (2019)
Cross-transfer (CT) is a phenomenon where the training of one limb enhances the performance in the untrained limb. Mirror therapy (MT) is the use of a mirror to create a reflective illusion of the corresponding limb movement. The study aims to determine whether the combination of MT with cross-transfer training (CTT) will increase cross-transfer effect (CTE) than just CTT alone. It was hypothesized that the addition of MT will increase CTE compared to CTT alone. 30 right-handed students (16 male, 14 females) from Nanyang Technological University were recruited. Participants were randomly assigned to an intervention or control group and tasked to complete 13 star tracing task (STT) – 3 with the dominant hand, 7 with the non-dominant hand, then 3 with the dominant hand. The intervention group performed the middle 7 STT with MT and CTT, while the control group conducted them with CTT alone. A head-cap containing functional near-infrared spectroscopy (fNIRS) technology that measures oxyhemoglobin (HbO) and deoxyhemoglobin concentration changes in the primary motor cortex (M1) was utilized. Reaction time (RT), accuracy, HbO concentration in both right and left hemispheres of M1 were measured. Significant difference in RT between Pretest and Posttest (p = 0.029) was found, but not found in accuracy (p = 0.90), HbO concentration in the right (p = 537) and left (p = 0.09) M1. In conclusion, addition of MT to CTT increasing CTE is only associated with RT improvement but not with other variables.